Bad land : an American romance - Raban, Jonathan (Pantheon Books, 1996)
Jonathan Raban ambles and picks his way across the Montana prairie, which had been called "The Great American Desert" until Congress offered 320-acre tracts of barren land to immigrants with stardust in their eyes. Raban's prose makes love to the waves of land, red dirt roads, and skeletons of homesteads that couldn't survive the Dirty Thirties. As poignant as any romance novel, there's heartbreak in the failed dreams of the homesteaders, a pang of destiny in the arbitrary way railroad towns were thrown into existence, and inspiration in the heroism of people who've fashioned lives for themselves by cobbling together homes from the ruined houses of those who couldn't make it. Through it all, Raban's voice examines and honors the vast open expanses of land and pays homage to the histories of families who eked out an existence.